(untitled) (Bangladesh Medical Journal, 2014)
The number of geriatric population, both in absolute value and as a proportion of the population has been rising since 1900. Currently 10% of world population is over 60 years, which is expected to increase to 20% by the year 2030. Life expectancy has been increasing for the population as a whole. Bangladesh is currently undergoing a demographic transition and the projection of the population ?60 years is rapidly increasing. Bangladeshs elderly population is one of the largest in the world in terms of absolute number. This change in population characteristics will have serious consequences on the society as well as on overall socio-economic development of the any country. In old age, high prevalence of morbidity is a common feature and health care expenditure for the elderly persons is much higher compared to the younger adult. There is a striking increase in the life expectancy and geriatric population is increasing day by day. On the othewr hand morbidity and mortality also increase with age. So, it is essential to know adequate information regarding geriatric population with their common health problems along with appropriate health care & preventive measures for the better quality of their health DOI: http://dx.doi.org/10.3329/bmj.v43i2.21395 Bangladesh Med J. 2014 May; 43 (2): 112-117